Decarbonization of Materials and Construction Processes: Editorial Note - González, Marcelo; Zegarra Marmanillo, Omar (Revista Ingeniería de Construcción, 2024)
The construction industry, responsible for 39% of global greenhouse gas emissions, faces an urgent need for decarbonization to meet Net Zero Emissions by 2050. Addressing this challenge in the context of issues like structural fragmentation and complex value chains requires innovative solutions and accelerated implementation. This special issue of the Revista Ingeniería de Construcción presents contributions from academics and practitioners across multiple countries, exploring critical decarbonization trends in the industry. Featured topics include low-carbon materials, recycling innovations, material design and performance, use of industrial by-products, and infrastructure quality assurance and preservation. The findings underscore the need for collaboration, innovation, and research to advance sustainable practices, aligning the construction sector with global decarbonization goals. This work invites stakeholders to contribute to transforming construction towards a more sustainable future.